Physiological and proteomic analysis of Lactobacillus casei in response to acid adaptation. (1st October 2014) - Wu, Chongde; He, Guiqiang; Zhang, Juan
Abstract: The aim of this study was to investigate the acid tolerance response (ATR) in Lactobacillus casei by a combined physiological and proteomic analysis. To optimize the ATR induction, cells were acid adapted for 1 h at different pHs, and then acid challenged at pH 3.5. The result showed that acid adaptation improved acid tolerance, and the highest survival was observed in cells adapted at pH 4.5 for 1 h. Analysis of the physiological data showed that the acid-adapted cells exhibited higher intracellular pH (pHi ), intracellular NH4 + content, and lower inner permeability compared with the cells without adaptation. Proteomic analysis was performed upon acid adaptation to different pHs (pH 6.5 vs. pH 4.5) using two-dimensional electrophoresis. A total of 24 proteins that exhibited at least 1.5-fold differential expression were identified. Four proteins (Pgk, LacD, Hpr, and Galm) involved in carbohydrate catabolism and five classic stress response proteins (GroEL, GrpE, Dnak, Hspl, and LCAZH_2811) were up-regulated after acid adaptation at pH 4.5 for 1 h. Validation of the proteomic data was performed by quantitative RT-PCR, and transcriptional regulation of all selected genes showed a positive correlation with the proteomic patterns of the identified proteins. Results presented in this study may be useful for further elucidating the acid tolerance mechanisms and may help in formulating new strategies to improve the industrial performance of this species during acid stress.